Influence of Viral Marketing, Celebrity Endorsement, and Brand Awareness on Purchase Decision of Specs in Sidoarjo - Saifudin, Muhamad Vicky; Yani, Muhammad; Indayani, Lilik (Airlangga Journal of Innovation Management, 2025)
This study aims to analyze the influence of viral marketing, celebrity endorsement, and brand awareness on purchasing decisions for Specs products in Sidoarjo. The development of digital technology and the high number of social media users in Indonesia open up great opportunities for companies to utilize digital marketing strategies. Specs, as one of the local sports shoe brands, faces tight competition with similar brands such as Eagle and League, so it requires an effective marketing strategy to maintain its market share. This study uses a quantitative approach with a survey method through a questionnaire to 100 respondents who use Specs products in Sidoarjo. The data analysis technique used is Partial Least Squares (PLS) to test the validity, reliability, and direct influence of the three independent variables on purchasing decisions. The results of the study show that viral marketing, celebrity endorsement, and brand awareness have a positive and significant influence on purchasing decisions. Viral marketing through social media is able to create interest and encourage purchasing decisions. Celebrity endorsement contributes to forming trust and product appeal through relevant public figures. Brand awareness makes it easier for consumers to recognize and remember products, thus encouraging purchasing actions. This study provides strategic implications for local companies in increasing the effectiveness of promotions in the digital era.